2015
DOI: 10.1007/s11751-015-0228-0
|View full text |Cite
|
Sign up to set email alerts
|

Hook plate fixation for acute acromioclavicular dislocations without coracoclavicular ligament reconstruction: a functional outcome study in military personnel

Abstract: The aim of our study was to evaluate the shoulder function after clavicular hook plate fixation of acute acromioclavicular dislocations (Rockwood type III) in a population group consisting exclusively of high-demand military personnel. This prospective study was carried out at a tertiary care military orthopaedic centre during 2012–2013 using clavicular hook plate for management of acromioclavicular injuries without coracoclavicular ligament reconstruction in 33 patients. All patients underwent routine implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 23 publications
3
49
0
1
Order By: Relevance
“…Even though the ROM interval after operation is different depending on the surgeon, about 2 to 3 weeks after operation are reported. 3,[9][10][11] Same as other studies, we usually started ROM exercise after 2 weeks postoperatively. However, the ROM just before implant removal was not good even though bony union and reduction were maintained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the ROM interval after operation is different depending on the surgeon, about 2 to 3 weeks after operation are reported. 3,[9][10][11] Same as other studies, we usually started ROM exercise after 2 weeks postoperatively. However, the ROM just before implant removal was not good even though bony union and reduction were maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many previous studies recommended implant removal after confirming stabilization during the follow-up. 3,5,9) According to Renger et al, 12) after fixation hook plate, 68% of patients had a complication of limited ROM and pain on ROM. In our study, we removed the hook plate at the mean postoperative period of 3.9 months (range, 3-5 months) in acromioclavicular dislocation and 4.2 months (range, 2-6 months) in lateral end fracture of the clavicle.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with hook plate xation, 25-50% suffer subacromial osteolysis or erosion [10,[19][20][21], which are the most common complications in hook plate xation. Subacromial osteolysis may result in more postoperative pain, discomfort, and an impaired functional outcome [9,10]. Yoon et al also reported a trend of an inferior functional score in patients with subacromial osteolysis [10], which indicated that greater stress on the hook tip may lead to a greater risk of subacromial osteolysis.…”
Section: Radiographic Outcomementioning
confidence: 99%
“…To date, the optimal surgical technique for ACJ dislocation is still under debate owing to controversy in reported outcomes. In a recent study, hook plate xation was reported to be a popular option that provides rigid xation and promotes nature scaring of the CC ligament, with the advantages of a simpler surgical technique, minimally-invasive access, and early resumption of normal activity [4,[7][8][9]. Despite these advantages, hook plate xation also has disadvantages, which include the need for implant removal surgery, subacromial impingement, subacromial osteolysis, and possible loss of reduction after implant removal, which may lead to complications such as a rotator cuff tear or an acromion fracture in patients with osteoporosis or those with a high activity level [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the optimal surgical technique for ACJ dislocation is still under debate owing to controversy in reported outcomes. In a recent study, hook plate xation was reported to be a popular option that provides rigid xation and promotes nature scaring of the CC ligament, with the advantages of a simpler surgical technique, minimally-invasive access, and early resumption of normal activity [4,[10][11][12]. Despite these advantages, hook plate xation alsohas disadvantages, which include the need for implant removal surgery, subacromial impingement, subacromial osteolysis, and possible loss of reduction after implant removal, which may lead to complications such as a rotator cuff tear or an acromion fracture in patients with osteoporosis or those with a high activity level [13][14][15].…”
Section: Introductionmentioning
confidence: 99%